Transient Left Bundle Branch Block Induced Acute Heart Failure as a Consequence of Ramus Intermedius Occlusion - Mehmet Eren; Yalcin Velibey (Annals of Noninvasive Electrocardiology)
ABSTRACT We present a case of acute decompensated heart failure due to transient left bundle branch block (LBBB) as a consequence of a ramus intermedius (RI) occlusion. A 63‐year‐old woman was admitted with acute onset of typical chest pain and pulmonary edema, a newly diagnosed LBBB and left ventricular (LV) systolic dysfunction. A coronary angiogram demonstrated critical stenosis at the osteal segment of RI. After successful coronary revascularization, LBBB was completely resolved, with an improvement in LV systolic function and symptoms. In terms of anatomical blood supply of the left bundle branch, transient LBBB as a consequence of an RI occlusion is unusual.